Can Planktonic Organisms be Useful for Determining the Drowning Depth in Fatal Diving Accidents? - Höbek, Ahmet; Toklu, Akın Savaş; Balkis-Ozdelice, Neslihan; Toklu Alıçlı, Benin (The Bulletin of Legal Medicine, 2020)
Objective: Although the triggering factors are various, most of the fatal diving accidents result in drowning. If drowning depth is known, it will contribute the clarification of underlying reasons of the accidents. In this experimental study, it has been investigated whether planktonic organisms can be used to determine the drowning depth in fatal diving accidents.Materials and Methods: Planktonic organisms in water samples taken from the surface and 30 meters depth of Marmara Sea were investigated. In addition, rats in one of the two groups of 8 Wistar Albino species were drowned in the water sample obtained from surface at pressure of 1 ATA, and rats in the second group were drowned in the water sample obtained from 30 m depth at a pressure of 4 ATA in a hyperbaric chamber and planktonic organism was investigated in the lungs of drowned rats.Results: In the examinations, 22 phytoplankton and 5 zooplankton taxa were detected in the samples obtained from the surface and 7 phytoplankton taxa were detected in the sample obtained from 30 m depth. In the autopsies planktonic organism was not found in the lungs of rats. It was observed that the lungs of the rats that drowned at 4 ATA were more bulging and bleeding. The absence of a planktonic organism in the lungs was thought to be due to the fact that the rats aspirated a very small amount of water and the plankton density in the samples was low....
Keywords: Diurnal Migration, Diving Accidents, Drowning, Planktonic Organisms